Embedded Ileal Fish Bone Removed via Deep Enteroscopy in a Patient with Abdominal Pain and Hematochezia: A Case Report - Hsin-Yang Chen; Chao-Feng Chang; Tien-Yu Huang; I-Hsuan Huang (Medicina)
Ingestion of foreign bodies is a prevalent issue in clinical practice, with fish bones being the predominant cause. While the upper gastrointestinal tract is commonly affected, small intestine impactions pose significant diagnostic challenges due to nonspecific symptoms and lack of awareness of foreign body ingestion. Herein, we describe a case presenting with recurrent, unexplained abdominal pain and hematochezia. Multiple diagnostic investigations, including esophagogastroduodenoscopy and colonoscopy, conducted over several months failed to identify the underlying cause until a retrograde single-balloon enteroscopy for obscure gastrointestinal bleeding revealed a 2.3 cm fish bone embedded in the distal ileum. The successful removal of the fish bone led to the resolution of the patient’s symptoms. This case highlights that foreign bodies in the small intestine can be a cause of hematochezia and emphasizes the growing importance of deep enteroscopy techniques in detecting and retrieving these foreign objects, thereby reducing the need for surgery.